Outsourcing contribution in The competitive advantage of enterprises - صيد ماجد (Finance and Business Economies Review, 2017)
the pace of global economic activity in recent decades, Have accelerated under the open world, dominated by severe competition, which has led industrial enterprises in the world -especially the developing- countries in the face of many challenges, particularly the obstacles of limited resources, small market shares, and the inability to marketing campaigns or research projects in light of the evolution of new technologies and innovation in all fields of their activities, and this is what made the option of outsourcing the most important strategic choices that has the ability to achieve industrial development, in view of the successful experiences in the most developed countries, Which makes it necessary for industrial enterprises in the third world countries to adopt this strategy, in order to develop and upgrade their products and increase their competitive advantage locally and internationally.